Pharmacokinetics and pharmacodynamics of TF‐505, a novel nonsteroidal 5α‐reductase inhibitor, in normal subjects treated with single or multiple doses - Fujita, Tomoe; Matsumoto, Yoshiaki; Kimura, Toshimi; Yokota, Shinichi; Sawada, Mika; Majima, Masataka; Ohtani, Yoshio; Kumagai, Yuji (British journal of clinical pharmacology, 2002)
Aims To assess the tolerability, pharmacokinetics and pharmacodynamics of a novel nonsteroidal   and   noncompetitive   inhibitor   of   type   I   and   type   II   5α‐reductases, (–)‐(S)‐4‐[1‐[4‐[1‐(4‐isobutylphenyl) butoxy]benzoyl]indolizin‐3‐yl]butyric acid (TF‐505), after single and multiple oral doses in healthy volunteers. Methods In the single‐dose study, six young adult males in each dose group received 25 mg or 50 mg of TF‐505, and six older males (≥ 40 years) in each dose group received 75 mg or 100 mg of TF‐505. The subjects were given the drug in ascending dose and in the fasting state. Six subjects also received 50 mg of TF‐505 after breakfast in a two‐period crossover manner. In the multiple‐dose study, six older males in each dose group received 12.5 mg or 25 mg TF‐505 after breakfast daily for 7 days. Plasma concentrations of TF‐505, dihydrotestosterone (DHT) and testosterone were measured. The pharmacokinetics of TF‐505 were analysed by a compartment model with first‐order absorption, first‐order elimination and a lag time. Pharmacokinetic and pharmacodynamic relationships were evaluated by indirect response modelling with inhibition of input. Results Maximum plasma concentration (Cmax) and the area under the concentration–time curve (AUC) increased proportionately after the single dose up to 50 mg and with the multiple doses. Linearity was not detected between 75 and 100 mg of TF‐505. Dose dependency was also noted for the effect of TF‐505 on DHT concentrations following single doses up to 50 mg and multiple doses. Plasma DHT concentrations decreased maximally to 58.2, 49.5, 54.2 and 49.8% of basal values at 8–12 h after single administration of 25, 50, 75 and 100 mg TF‐505, respectively, and to 60.5 and 49.4% at the 7th and 5th dose following multiple doses of 12.5 and 25 mg TF‐505, respectively. The predicted effect curves matched the observed data when the indirect response model was applied to the time course of the suppressant effect of TF‐505 on plasma DHT concentrations after both the single and multiple studies. Fifty percent inhibitory concentrations (IC50) of 0.82, 1.48, 1.31 and 0.88 µ g ml−1, zero‐order rate constants for the onset of plasma DHT concentration changes (kin) of 17.8, 17.4, 17.0 and 10.7% h−1 and first‐order rate constants   for   increase   in   plasma   DHT   concentrations   to   basal   values   (kout)   of   0.17,   0.16,   0.17   and   0.10 h−1   for   the   single   study   at   doses   of   25,   50,   75   and 100 mg, respectively, were attained. In the multiple‐dose study, IC50s were 1.74 and 1.49 µg ml−1 for the 12.5 and 25 mg doses, respectively. No serious adverse events related to TF‐505 were observed. Conclusions TF‐505 was well tolerated in healthy male volunteers. Accumulation of TF‐505 in plasma was not observed during multiple dosing. The indirect response model described the relationships between pharmacokinetics and pharmacodynamics of TF‐505. Such modelling is expected to yield an appropriate dosage regimen in subsequent clinical trials.